2022
DOI: 10.1126/science.abm3371
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interplay between metal nanoparticles and oxide support under redox conditions

Abstract: The dynamic interactions between noble metal particles and reducible metal-oxide supports can depend on redox reactions with ambient gases. Transmission electron microscopy revealed that the strong metal-support interaction (SMSI)–induced encapsulation of platinum particles on titania observed under reducing conditions is lost once the system is exposed to a redox-reactive environment containing oxygen and hydrogen at a total pressure of ~1 bar. Destabilization of the metal–oxide interface and redox-mediated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
168
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(172 citation statements)
references
References 77 publications
3
168
1
Order By: Relevance
“…16 While some authors claim that the encapsulation can also be reversed by O2 annealing 6,17,[18][19][20] , others report an oxidation of the particles and/or thickening of the titania encapsulation layer under such conditions. 7,[21][22][23] In their pioneering work on SMSI, Tauster et al reported that the change in chemisorption behavior of a reduced Pd/TiO2 powder catalyst upon O2 annealing at 773 K is completely reversible. 6 Similarly, different authors found restored H2 chemisorption after annealing reduced TiO2 decorated with noble metal powder catalysts at elevated O2 pressures and temperature (>70 Torr O2, > 573 K).…”
Section: Introductionmentioning
confidence: 99%
“…16 While some authors claim that the encapsulation can also be reversed by O2 annealing 6,17,[18][19][20] , others report an oxidation of the particles and/or thickening of the titania encapsulation layer under such conditions. 7,[21][22][23] In their pioneering work on SMSI, Tauster et al reported that the change in chemisorption behavior of a reduced Pd/TiO2 powder catalyst upon O2 annealing at 773 K is completely reversible. 6 Similarly, different authors found restored H2 chemisorption after annealing reduced TiO2 decorated with noble metal powder catalysts at elevated O2 pressures and temperature (>70 Torr O2, > 573 K).…”
Section: Introductionmentioning
confidence: 99%
“…The face-centered cubic crystal structure of Au is lost when exposing the gold sample to the hydrogen conditions 38 . Also, platinum particles could be influenced by the redox chemical environment to form twin planes 39 . Furthermore, for the Au/TiO 2 catalyst in the CO oxidation reaction, the reconstruction of Au NPs with the major (111) and (100) facets of the gold NPs exposed by the reactants has been reported 42 .…”
Section: Resultsmentioning
confidence: 99%
“…used in situ TEM to observe the Pt/TiO 2 system under different atmospheres. [ 50 ] Noticeably, it was the first time that the SMSI process was observed under real working conditions, which provides new insights into understanding the SMSI process. First, the classical SMSI with the formation of encapsulation overlayer was constructed in pure H 2 atmosphere at 600 °C, and the overlayer became thicker during this process, accompanied with no apparent change in the shape of Pt NPs.…”
Section: Understandings and Extensions Of Smsimentioning
confidence: 99%
“…Reproduced with permission. [ 50 ] Copyright 2022, American Association for the Advancement of Science.…”
Section: Understandings and Extensions Of Smsimentioning
confidence: 99%
See 1 more Smart Citation